The Economics of Being Young and Poor: How Homeless Youth Survive in Neo-liberal Times - Hughes, Jean (2010)
Based upon in-depth interviews with 34 youth in Halifax and seven service providers in St. John's, Montreal, Hamilton, Toronto, Winnipeg, and Calgary, the findings of this study suggest that labor occurs within a particular street context and street culture. Formal and informal work can be inter-related, and despite the hardships they experience, young people who are homeless or who are at-risk of homelessness can respond to their circumstances with ingenuity, resilience and hope. Often street-involved and homeless young people are straddling formal and informal work economies while mediating layers of external and internal motivations and tensions. The reality is that the participants in this study cannot very easily engage in formal work. There is a dearth of meaningful formal work available, and when living homeless there are many challenges to overcome to maintain this work. In addition, there are few employers willing to risk hiring an individual who is without stable housing, previous employment experiences and, most likely, limited formal education. Therefore, street youth are left with informal work that provides them with survival money, basic needs, and a sense of citizenship, but which also invites belittlement, harassment, and mockery